Individual values and attitudes to development - Pojarliev, Alexander (Leadership, Society, Strategic Visions, 2021)
Typically, dreams refl ect the achievement of a better and desirable state that can be considered as a form of development. One possible typology of different views of a desirable state is through the prism of values as criteria for choice and motivating factors of behavior. The present study aims to reveal the specifi cs of the value orientations of Bulgarian respondents with the help of Schwarz’s internationally approved structural model of the basic values .The research seeks to address the question of how individual values relate to perceiving the importance of personal development and resources as time and money that people are willing to devote to it. The study covers 417 respondents and its methodology is based on a survey that includes the Schwarz’s Portrait Values Questionnaire (PVQ).